Exploration of Al-Hallaj's Thought: Window on Religious Pluralism in Islam - Eliza, Eliza; Nelmawarni, Nelmawarni; Efendi, Efendi; Tri Hadi, Rahmad (UIN Sunan Kalijaga Yogyakarta, 2024)
This research aims to describe and explore the thinking of Wahdat al-Adyan al-Hallaj. The method used in this research is descriptive-analytical. The primary data used in this research are the works of al-Hallaj. Meanwhile, secondary data in this research are books, journal articles and other websites that discuss al-Hallaj's thoughts. The research results show that there are efforts to deconstruct Islamic Sufism al-Hallaj by pluralist circles. The accusation of al-Hallaj as the father of pluralism in Islam cannot be proven. This is due to misunderstanding and needing to be more comprehensive in understanding al-Hallaj's expressions in his verses and aimed at the interests of Western liberalization with efforts to interpret the text and misappropriation of language from Transcendent Unity of Religion become Wahdat al-Adyan. So, concept Wahdat al-Adyan what is claimed to be the concept of religious pluralism in the Western or Orientalist version of Islam is a misunderstanding. In Islam there is no such thing as religious unity (transcendent unity), what exists instead is al-Hallaj's experience in understanding religious differences. However, understanding Wahdat al-Adyan which was introduced by al-Hallaj, in essence, the existing religions have the same aim, namely to obtain calm, peace and happiness in their spiritual dimension by serving their God according to their respective beliefs. Therefore, it is not permissible to judge and criticize other religions, and instead recommend that someone be obedient and consistent in their respective religions, as well as open, tolerant and pluralist religious awareness.